HUBUNGAN ANTARA KREATIVITAS GURU DALAM PEMBELAJARAN DENGAN MINAT BELAJAR PESERTA DIDIK DI SD INPRES 6 SAUSU - Utami, Sesilia Tri; Sudarsana, Wayan; Narayanti, Putu Satya (STAH Dharma Sentana Sulawesi Tengah, 2025)
This study aims to examine the relationship between teacher creativity in teaching and students' interest in learning at SD Inpres 6 Sausu, as well as students' responses to teacher creativity. The study employs a quantitative correlational approach, with sampling selected using Stratified Random Sampling technique. The instruments used include observation sheets, questionnaires, documentation, and validation sheets.The results of the study show that teacher creativity at SD Inpres 6 Sausu is categorized as excellent, with an average percentage of 89.2%. Hypothesis testing using Pearson's product-moment correlation reveals a significant relationship between teacher creativity and students' interest in learning, with a significance value of 0.000 (Sig. 2-tailed < 0.05) and a Pearson correlation coefficient of 0.622, indicating a strong relationship. Furthermore, the overall average response percentage reached 89.01%, indicating that the higher the teacher's creativity in teaching, the better the responses given by the students. In conclusion, teacher creativity has a significant relationship with students' interest in learning.